PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA PT DANAMAS MANDIRI INVESTA - Rezky Muhammad Islam; Syahrum Agung; M. Azis Firdaus (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of job compensation and job satisfaction on the work productivity of PT. Danamas Mandiri Investa. This type of research is quantitative. The population of this research is the employees of PT. Danamas Mandiri Investa. The analysis used is a quantitative technique using a saturated sampling technique with a population of 30 respondents. The instrument of this research is a questionnaire. The results of the research instrument test using multiple regression analysis test, t test, and f test. The results of the analysis show that job compensation and job satisfaction have a significant effect on work productivity with the results of multiple regression analysis of Y = 4,527 + 0,284 X1 + 0,641 X2. The results of the work compensation t test showed that tcount > t table 2,183 > 1,703 meaning Ho1 was rejected, and Ha1 was accepted, the job satisfaction t test was 5,453 > 1,703 meaning Ho2 was rejected and Ha2 was accepted, and the f test results were 38,300 > 3,34 meaning Ho3 is rejected and Ha3 is accepted. Based on the results of these data, it can be concluded that work compensation and job satisfaction have an effect on work productivity in PT. Danamas Mandiri Investa.”